Rise of the sexual libido in old age - Valdizan, Hermilio (1926)
Known sources of sexuality and its variations along the journey of life we thought, Dr. Delgado and I live in the interest of the knowledge of the terminal developmental stage of that sexuality. And so, for some years, we have observed, with maximum care, senile libido of our patients, both in civil practice and nosocomial.